Terrorism in Pakistan: Under the Framework of Causal Layered Analysis - Khan, Muhammad; Naseer, Noreen (The Lighthouse Journal of Social Sciences, 2023)
Terrorism is a concern of the world by realizing it as an issue in the past present and future; there is a need to challenge prevailing circumstances with the vision of an alternative future. The case study of terrorism in Pakistan is used under the framework of Causal Layered Analysis to find out the approach for a better future by using different parameters of knowledge. This article discusses the myths and worldviews surrounding terrorism and how they contribute to the global problem. The author suggests that there is a need for extended research to explore more ways to understand and perceive the intensity and implications of terrorism. The paper also discusses the need for a change in discourse to promote love, peace, and harmony among people and eliminate the jihadi culture. The study seems to be focused on analyzing the systemic causes of terrorism and identifying hegemonic worldviews and myths to attain a narrative to deconstruct the meta-level of future terrorism. Overall, the study appears to be discussing the need for a more nuanced and comprehensive understanding of terrorism and its underlying causes to develop effective counter-terrorism initiatives.